First record of greater flamingo Phoenicopterus roseus from south east coastal, Bangladesh - Ahmed, Asif; Mahmud, Humayra (Bangladesh Journal of Zoology, 2018)
Abstract not available Bangladesh J. Zool. 45(2): 185-188, 2017